21-Year-Old Female with Pneumothorax and Massive Air Leak Following Blunt Trauma; a Photo Quiz - Shirinzadeh-Dastgiri, Ahmad; Saberi, Ali; Vakili, Mohammad; Marashi, Sayed Mahdi (Archives of Academic Emergency Medicine, 2022)
A 21-year-old female presented to the emergency department, about 20 minutes after a motorcycle accident. She was agitated and complaining of shortness of breath. Her vital signs were: heart rate 110 bpm, respiratory rate 32/minute, blood pressure 89/67 mmHg, oxygen saturations 79% on room air, temperature 36.5°C and GCS 15. Chest auscultation revealed decreased breath sounds on the left side. The diagnosis of pneumothorax was made for the patient and a left thoracostomy tube was inserted; however, massive air leak was noted and the clinical symptoms did not improve. Computed tomography scan of the chest in the mediastinal window showeda doubtful pathology, crumpled laminated membrane.